Toward a Global History of Latin America's Revolutionary Left - Martín Álvarez, Alberto; Harmer, Tanya (Book collections on Project MUSE., 2021)
"This volume showcases new research on the global reach of Latin American revolutionary movements during the height of the Cold War, mapping out the region's little-known connections with Africa, Asia, and Europe"--